2004
DOI: 10.1097/00001756-200410050-00004
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve regeneration in polyglycolic acid–chitosan conduits coated with recombinant L1-Fc

Abstract: Autografts have been extensively studied to facilitate optic nerve (ON) regeneration in animal experiments, but the clinical application of this approach to aid autoregeneration has not yet been attempted. This study aims to explore the guided regeneration by an artificial polyglycolic acid-chitosan conduit coated with recombinant L1-Fc. Consistent with previous studies; in vitro assay showed that both chitosan, a natural biomaterial, and the neural cell adhesion molecule L1-Fc enhanced neurite outgrowth. Rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…The adhesion molecule L1 favors axonal growth in an inhibitory environment (Castellani et al, 2002;Dong et al, 2002;Fransen et al, 1998;Lemmon et al, 1989;Roonprapunt et al, 2003;Xu et al, 2004;Zhang et al, 2005), promotes neurite outgrowth, and displays survival-promoting effects on cultured central nervous system neurons (Chen et al, 1999;Dong et al, 2002;Dong et al, 2003;Lemmon et al, 1989;Lindner et al, 1983;Rathjen and Rutishauser, 1984). We found that T4as-NPCs overexpress L1 and survive better in the lesioned area, suggesting that L1 positively influences NPC survival, even after grafting into a hostile environment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The adhesion molecule L1 favors axonal growth in an inhibitory environment (Castellani et al, 2002;Dong et al, 2002;Fransen et al, 1998;Lemmon et al, 1989;Roonprapunt et al, 2003;Xu et al, 2004;Zhang et al, 2005), promotes neurite outgrowth, and displays survival-promoting effects on cultured central nervous system neurons (Chen et al, 1999;Dong et al, 2002;Dong et al, 2003;Lemmon et al, 1989;Lindner et al, 1983;Rathjen and Rutishauser, 1984). We found that T4as-NPCs overexpress L1 and survive better in the lesioned area, suggesting that L1 positively influences NPC survival, even after grafting into a hostile environment.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, it has been proposed that T4 exerts its neuropromoting effects, at least partly, via mechanisms that involve activation of the cell adhesion molecule Journal of Cell Science 122 (22) L1. The neuronal recognition molecule L1 has been shown to favor axonal growth in an inhibitory environment (Castellani et al, 2002;Chen et al, 2007;Roonprapunt et al, 2003;Xu et al, 2004;Zhang et al, 2005). On the basis of these observations, we investigated whether the functional improvement of mice transplanted with T4as-NPCs might be due to increased L1 expression.…”
Section: Transplanted T4as-npcs Survive and Differentiate In Injuredmentioning
confidence: 99%
“…it is downregulated on myelinated axons and re-expressed in regenerating axons after spinal cord injury [64,65] . Exogenous L1CAM is beneficial in promoting axon growth and functional recovery after spinal cord injury [66] and optic nerve lesion [67] and is involved in the regenerative growth of Purkinje cell axons in vivo [68] .…”
Section: Cell Adhesion Moleculesmentioning
confidence: 99%
“…We have shown previously that L1 influences differentiation of neural stem cells into neurons in vitro (Dihné et al, 2003). Furthermore, L1 has been shown to promote functional recovery in adult rats after contusion-induced spinal cord injury (Roonprapunt et al, 2003) and optic nerve lesion (Xu et al, 2004) and is involved in regenerative growth of Purkinje cell axons in vivo (Zhang et al, 2005), thus overcoming regeneration-adversive cues that prevail in the CNS of adult mammals.…”
Section: Introductionmentioning
confidence: 99%